Pengaruh Perbedaan Suhu terhadap Pertumbuhan dan Kelangsungan Hidup Larva Tiram Mutiara (Pinctada Maxima) - Maria Selvia Froni; Priyo Santoso; Yulianus Linggi (Student Research Journal, 2026)
The pearl oyster (Pinctada maxima) is a high-value aquaculture commodity whose hatchery success is strongly influenced by environmental conditions, particularly temperature. This study aimed to determine the effect of different temperatures on the growth and survival rate of Pinctada maxima larvae. The research was conducted at PT Timur Otsuki Mutiara (PT. TOM), Kupang Regency, East Nusa Tenggara, using a Completely Randomized Design (CRD) consisting of three temperature treatments: A (28°C), B (29°C), and C (30°C), each with three replications. The observed parameters included survival rate, absolute growth, dorsal–ventral specific growth rate, anterior–posterior specific growth rate, and water quality. Data were analyzed using Analysis of Variance (ANOVA). The results showed that temperature had a significant effect (P<0.05) on the survival rate and specific growth rate of the larvae. The 28°C treatment produced the highest survival rate (22.44%), dorsal–ventral specific growth rate (4.97%), and anterior–posterior specific growth rate (5.13%). The highest absolute growth was also recorded at 28°C, reaching 121.67 µm; however, no significant differences were observed among treatments (P>0.05). Water quality parameters remained within the optimal range for larval rearing throughout the study. Based on the research results, it can be concluded that 28°C is the optimum temperature for supporting the growth and survival of Pinctada maxima larvae, whereas increasing the temperature up to 30°C tends to reduce larval performance.